Evaluating Safety Culture Maturity in Indonesian Petrochemical Industry to Strengthen Occupational Health Systems - Putu Nadi Astuti; Zulkifli Djunaidi; Arifah Alfiyyah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: This study aimed to assess the maturity of safety culture implementation across petrochemical companies in Indonesia. By using a mixed-methods to provide a comprehensive understanding of occupational health and safety risks in high-hazard industries. The petrochemical sector being prone to workplace accidents and process related to incidents. The objective was to identify the maturity level of safety practices and highlight priority areas for improvement, addressing gaps in existing literature on safety culture measurement in industrial settings. Methods: This cross-sectional mixed-methods study involved surveys and observations conducted across 10 petrochemical companies in 2024. A total of 513 participants were enrolled, and data were collected through validated questionnaires, plant visits, and document reviews. Ethical approval was obtained from the Faculty of Public Health Universitas Indonesia and participants provided informed consent. Results: The primary outcome of the study was the maturity level of safety culture, which most respondents rated as “Generative.” Based on company type significant differences (p < 0.05) were found in commitment. While other variables such as information, organizational learning, employee participation, and communication showed no significant differences. There were no significant differences based on industry type and role type for each variable. The findings from qualitative method indicate that most companies have implemented both national safety standards namely SMK3 (Occupational Health and Safety Management System) and international systems (including ISO 45001, OSHA PSM, ILO PSM, and Responsible Care). Conclusion: In conclusion, the importance of a mature safety culture in supporting occupational health and safety practices and highlights the need for continuous improvement in workplace safety systems. Future studies should explore interventions that strengthen these dimensions, helping reduce occupational risks in the petrochemical industry.